Model pelayanan air bersih perdesaan - Rini Dorojati; Nuraini Dwi Astuti; Hartono Hartono (Masyarakat, Kebudayaan dan Politik, 2016)
Low coverage of clean water in Indonesia leads to minimum consumption of clean water with proper health requirement. Increasement of clean water coverage is undergoing an effort from independent community in society. This research aims to find a service model of clean water for group based rural communities. Type of this research is descriptive qualitative, with research object is clean water independent provider group, Oyo Wening Santosa community, in a village called Bunder, district of Patuk, Gunung Kidul. Data was gathered by document utilization, parsitipatory observation, in-depth interview, and focus group discussion. Data was analyzed with qualitative method. This research shows that clean water coverage organized by communiy Oyo Wening is a model of sinergy for organization that was established by concern from society and government support, emerge in a program called “Sistem Penyediaan Air Minum Ibu Kota Kecamatan” (SPAM IKK). There are 1170 households channel subscribers spread across four villages. The service procedures are applied based on local conditions. This service has some drawbacks, namely the limited knowledge of the officer, the legality of which is not owned by the organization, facilities and infrastructure, and the relatively low tarrif, Rp 3,500 per m3. In conclusion, rural water services with the model applied in Oyo Wening Sentosa showed a changing trend in people's access to clean water and the local economy has increased. The legality of the business management of water services should become a priority for the stakeholders to ensure the realization of excellent service in providing clean water.